Trypanosoma cruzi-derived exovesicles contribute to parasite infection, tissue damage, and apoptotic cell death during ex vivo infection of human placental explants - Fernández-Moya, Alejandro; Oviedo, Bielca; Liempi, Ana; Guerrero-Muñoz, Jesús; Rivas, Cristian; Arregui, Rocío; Araneda, Sebastian; Cornet-Gomez, Alberto; Maya, Juan Diego; Müller, Marioly; Osuna, Antonio; Castillo, Christian; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Trypanosoma cruzi, the causative agent of Chagas disease, can be congenitally transmitted by crossing the placental barrier. This study investigates the role of T. cruzi-derived exovesicles (TcEVs) in facilitating parasite infection and the consequent tissue damage and apoptotic cell death in human placental explants (HPEs). Our findings demonstrate that TcEVs significantly enhance the parasite load and induce tissue damage in HPEs, both in the presence and absence of the parasite. Through histopathological and immunohistochemical analyses, we show that TcEVs alone can disrupt the placental barrier, affecting the basal membrane and villous stroma. The induction of apoptotic cell death is evidenced by DNA fragmentation, caspase 8 and 3, and p18 fragment immunodetection. This damage is exacerbated when TcEVs are combined with T. cruzi infection. These findings suggest that TcEVs play a critical role in the pathogenesis of congenital Chagas disease by disrupting the placental barrier and facilitating parasite transmission to the fetus. This study provides new insights into the mechanisms of transplacental transmission of T. cruzi and highlights the potential of targeting TcEVs as a therapeutic strategy against congenital Chagas disease.